2014
DOI: 10.1177/2053369114544729
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differences in the menopausal experience of Chinese women

Abstract: As Chinese women age and continue working longer, they will spend increasing amounts of time postmenopausal and in the workplace. The development of worksite-based health programmes would be advantageous to female workers of menopausal age in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Occupational classification may affect menopausal onset, with manual workers experiencing it earlier than white collar employees in two studies (42,43), although the relationship between early onset menopause and heavy physical work conditions is disputed elsewhere (44). Non-white collar occupational status may be a risk factor in the burdensomeness of menopausal symptoms (15). From a wider economic purview, Mvundura's (2007) (45) econometric study of menopause and labour market outcomes ascertained that menopause creates an increased supply of women in the US labour market, and that women who are perimenopausal are more likely to be self-employed than those who are postmenopausal.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Occupational classification may affect menopausal onset, with manual workers experiencing it earlier than white collar employees in two studies (42,43), although the relationship between early onset menopause and heavy physical work conditions is disputed elsewhere (44). Non-white collar occupational status may be a risk factor in the burdensomeness of menopausal symptoms (15). From a wider economic purview, Mvundura's (2007) (45) econometric study of menopause and labour market outcomes ascertained that menopause creates an increased supply of women in the US labour market, and that women who are perimenopausal are more likely to be self-employed than those who are postmenopausal.…”
Section: Resultsmentioning
confidence: 97%
“…Many surveys have noted that women who are employed (compared to women not in paid employment) report fewer (5,8,9,10,11,12) and/or less severe, intense or burdensome (13,14,15) symptoms, exhibit different health behaviour and greater knowledge in relation to menopause (16,17,18,19), and reach natural menopause at a later age (20,21,22,23). (31) and use of hormone replacement therapy (HRT) has also been linked to work status in some studies, suggesting that women in paid employment are more likely to take HRT (32,33).…”
Section: Resultsmentioning
confidence: 98%
“…For women in casual work, musculoskeletal symptoms of joint and muscle stiffness, aches, and pains, particularly in the legs, back, shoulders and neck, were the commonest and worst symptom of the menopause [ 22 , 23 ]. Within cohorts of employed women by contrast, hot flushes were slightly [ 33 ] or significantly [ 31 ] more prevalent.…”
Section: Resultsmentioning
confidence: 99%
“…Although the significant associations between demographic factors and reporting menopausal symptoms have been confirmed in the literature, the direction of the associations was inconsistent. One group of studies reported that those with low educational attainment or homemakers were more likely to report menopausal symptoms (Gold et al 2006; Huseth-Zosel, Strand, and Perry 2014). The other group of studies reported that those who were employed or had higher levels of education or income were more likely to report menopausal symptoms (Bawar et al 2013).…”
Section: Discussionmentioning
confidence: 99%